2021
DOI: 10.3390/jof7060430
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Highly Efficient Acid-Stable Xylanase and β-Xylosidase System from the Fungus Byssochlamys spectabilis ATHUM 8891 (Paecilomyces variotii ATHUM 8891)

Abstract: Two novel xylanolytic enzymes, a xylanase and a β-xylosidase, were simultaneously isolated and characterized from the extracellular medium of Byssochlamys spectabilis ATHUM 8891 (anamorph Paecilomyces variotii ATHUM 8891), grown on Brewer’s Spent Grain as a sole carbon source. They represent the first pair of characterized xylanolytic enzymes of the genus Byssochlamys and the first extensively characterized xylanolytic enzymes of the family Thermoascaceae. In contrast to other xylanolytic enzymes isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Endo-1,4-xylanase (xylanase) activity was determined as described previously [ 21 ]. Briefly, 50 μL of properly diluted enzyme was added to 450 μL of 20 g·L −1 oat spelt xylan (Sigma, St. Louis, MO, USA) in 50 mM citrate-phosphate buffer (pH 7.0) and placed in a thermoshaker (TS-100, BOECO, Hamburg, Germany) operating at 900 rpm and 60 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Endo-1,4-xylanase (xylanase) activity was determined as described previously [ 21 ]. Briefly, 50 μL of properly diluted enzyme was added to 450 μL of 20 g·L −1 oat spelt xylan (Sigma, St. Louis, MO, USA) in 50 mM citrate-phosphate buffer (pH 7.0) and placed in a thermoshaker (TS-100, BOECO, Hamburg, Germany) operating at 900 rpm and 60 °C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent work has shown that thermoacidophilic xylanase enzyme of Aspergillus tubingensis possessed an optimum pH and temperature of 5.0 and 50 o C, respectively (Intasit et al, 2022). In another study, Galanopoulou et al (2021) have characterized thermophilic, acid-stable xylanase from Byssochlamys spectabilis, optimally working at 65 o C and pH 3.5 (Galanopoulou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%